2022
DOI: 10.1093/ijpp/riab079
|View full text |Cite
|
Sign up to set email alerts
|

Assessing community pharmacists’ attitudes towards identifying opportunities for deprescribing in clinical practice in Ireland

Abstract: Objectives The main objective of this study was to assess community pharmacists’ thoughts regarding the role they can play in effectively integrating deprescribing into clinical practice in Ireland. The aim was to assess pharmacists’ (1) knowledge of deprescribing, (2) confidence in deprescribing, (3) attitudes towards deprescribing and (iv) barriers and facilitators to deprescribing in a community pharmacy setting. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In our study, only one in four respondents thought that education in medical school had prepared them for deprescribing in clinical practice. Education is of utmost importance as it is one of the main facilitators of deprescribing as expressed in our study and also earlier by Irish pharmacists [ 35 ]. Recently, a review on geriatric medicine topics in medical curriculums [ 36 ] was published.…”
Section: Discussionsupporting
confidence: 66%
“…In our study, only one in four respondents thought that education in medical school had prepared them for deprescribing in clinical practice. Education is of utmost importance as it is one of the main facilitators of deprescribing as expressed in our study and also earlier by Irish pharmacists [ 35 ]. Recently, a review on geriatric medicine topics in medical curriculums [ 36 ] was published.…”
Section: Discussionsupporting
confidence: 66%
“…Resources such as time, staff and documentation were described as insufficient in Irish long-term care facilities and a lack of communication and co-ordination between healthcare settings was believed to be responsible for the fragmented care for long-term care patients. These environmental barriers echo challenges identified in Irish primary care settings [ 46 , 47 ] and in international long-term care settings. [ 48 53 ].…”
Section: Discussionmentioning
confidence: 96%
“…Even though majority of healthcare providers in the present study know the term deprescribing, and for whom and for why it employed, more than half of them said that they did not have su cient knowledge on how to do with deprescribing. On contrary, the study conducted in a community pharmacy in Ireland showed that pharmacists had su cient knowledge about deprescribing (25). The difference might rise from the composition of study participants where we included all healthcare providers supposed to have direct or indirect role in patients' medication review.…”
Section: Discussionmentioning
confidence: 95%